(untitled) (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2023)
Introduction: Cervical tuberculous spondylitis is a rare disease and low prevalence in all spinal diseases. The cervical region is more vulnerable to volume addition because of tight space in the spinal canal that could damage neurological function. Case description: A 25-year-old female with pain in the posterior of her neck. The pain was accompanied by numbness and tingling that radiated from the hind neck to the left hand. She had no systemic symptoms. She also had a small-sized lump in her hind neck. The patient admitted that she had undergone an antituberculosis drug regimen three months before. The neurological and physical examination revealed hypesthesia in the left upper limb and gibbus in the hind-neck which was approximately one centimeter in diameter. MRI examination revealed that suspicion of cervical tuberculous spondylitis. The patient had undergone debridement laminectomy and posterior stabilization surgery. The pathology impression revealed that supporting tuberculous chronic specific spondylitis. Discussion: Progresivity of abscess led to necrosis of the bone and its surrounding tissue that could cause deformities and neurological symptoms. Conclusion: Cervical tuberculous spondylitis is a very rare case, because it used to be in lumbar or thoracic vertebrae. If this case had been left untreated, it would have a severe prognosis.